Correlation between Plasma Macrophage Migration Inhibitory Factor Levels and Long-Term Prognosis in Patients with Acute Myocardial Infarction Complicated with Diabetes - Haiyi Yu; Xinyu Wang; Xiangning Deng; Youyi Zhang; Wei Gao (Hindawi Limited, 2019)
Macrophage migration inhibitory factor (MIF), a widely expressed pleiotropic cytokine, is reportedly involved in several cardiovascular diseases, in addition to inflammatory diseases. Plasma MIF levels are elevated in the early phase of acute cardiac infarction. This study is aimed at investigating the correlation between plasma MIF levels and cardiac function and prognosis in patients with acute ST-segment elevation myocardial infarction (STEMI) with or without diabetes mellitus. Overall, 204 patients with STEMI who underwent emergency percutaneous coronary intervention were enrolled: 57 and 147 patients in the diabetes and nondiabetes STEMI groups, respectively. Sixty-five healthy people were selected as controls. Plasma MIF levels were measured at the time of diagnosis. Basic clinical data and echocardiographic findings within 72 h of admission were collected. Patients were followed up, and echocardiograms were reviewed at the 12-month follow-up. Plasma MIF levels were significantly higher in the diabetes and nondiabetes STEMI groups than in the control group and in patients with Killip grade≥II STEMI than in those with Killip grade I. Plasma MIF levels were negatively correlated with the left ventricular ejection fraction (LVEF) of myocardial infarction in patients with or without diabetes in the acute phase of infarction, whereas the left ventricular diastolic dysfunction (LVDD) was positively correlated. MIF levels in the nondiabetes STEMI group were positively correlated with N-terminal pro-b-type natriuretic peptide levels and were associated with LVEF and LVDD at the 12-month follow-up. The risk of adverse cardiovascular and cerebrovascular events was significantly higher in the MIF high-level group (≥52.7 ng/mL) than in the nondiabetes STEMI group 36 months after presentation. Thus, MIF levels in STEMI patients with or without diabetes can reflect acute cardiac function. In STEMI patients without diabetes, MIF levels can also indicate cardiac function and long-term prognosis at the 12-month follow-up.